DAMPAK PEREKONOMIAN RUMAH INDUSTRI NUGGET DI MASA PANDEMI COVID-19 DI DESA KALANGANYAR LEBAK BANTEN - Usmaedi Usmaedi; Yadi Heryadi; Ade Eka Anggraini (Nindikayla Institute, 2023)
The covid-19 virus has had a lot of impact on Indonesian society, especially in the economic sector, not only in large industries, the corona virus pandemic has made home industry businesses nervous. The UMKM products that are produced by the people of Kalanganyar Village are food products that are home made / home industry managed by Mrs. Sukaesih. The growth and development of the home industry that produces nuggets is done by the family and neighbors of the Sukaesih mother. The impact of the covid-19 virus greatly affects the home industry of nuggets in its production, marketing, and income from the production of these nuggets. Barokah nugget home industry has decreased by about 30%. The purpose of this report is to determine the impact of the Covid-19 pandemic on nugget production, marketing, employee decline, and nugget production income. This activity was carried out using the method of socializing the community regarding education on the prevention of the covid-19 virus, as well as observation and interviews with a home industry in Kalanganyar Village. The result of this activity is that the community cares more about the surrounding environment and is more concerned about the prevention of the Covid-19 virus, and the public is more aware of government regulations regarding health protocols in new life (new normal) and applied in everyday life